Subjek Dakwah Islam Dalam Perspektif Al-Qur’an - A. Fikri Amiruddin Ihsani (Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
Islamic da’wah subjects is person who conveys, teaches and practices Islamic teachings. It’s very important and interesting to study and learn more deeply. It can understand and deepen Islamic teachings are expected to be able to minimize message of preaching that isn’t in accordance with Islamic teachings. Based on context, the purpose of this study is to answer the question of how Islamic da’wah subjects in perspective of the Qur’an. This study uses qualitative research methods using descriptive analytical. To be able to study this phenomenon in detail, researchers quote of the Qur'an verses that allude to issue of Islamic da'wah. To be able to understand these verses, researcher also studies harmonious interpretations including of al-Jalalain interpretations, al-Nukat wa al-Uyun interpretations, al-Muyassar interpretations, Shaykh Abdurrahman interpretations, Ibnu Katsir interpretations, Anwar al-Tanzil wa Asrar al Ta'wil interpretations, al-Misbah interpretations, Madarik al-Tanzil wa Haqoiq at-Ta'wil interpretations, and Religion Ministry interpretations. Based on perspective of the Qur'an, the results obtained that Islamic da'wah subjects is perpetrators of da'wah as the heirs of the prophets who carry out mission of broadcasting Islamic teachings, inviting acts of ma'ruf and preventing acts of munkar. Besides that, what is said or delivered Islamic da'wah subjects must be conveyed from attitudes and actions. Therefore, before they plunge into people to preaching, it’s better to understand and study Islamic teachings well. Keywords: Da'wah subjects, Da'i, al-Qur'an.